2013
DOI: 10.1007/s12016-012-8348-5
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Inflammatory Adverse Reactions Related to Soft Tissue Filler Injections

Abstract: An ever-increasing number of persons seek medical solutions to improve the appearance of their aging skin or for aesthetic and cosmetic indications in diverse pathological conditions, such as malformations, trauma, cancer, and orthopedic, urological, or ophthalmological conditions. Currently, physicians have many different types of dermal and subdermal fillers, such as non-permanent, permanent, reversible, or non-reversible materials. Despite the claims of manufacturers and different authors that fillers are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
105
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 67 publications
2
105
0
1
Order By: Relevance
“…However, our study, in line with other studies [2][3][4][5], has shown that dermal filler treatments can have severe side effects and cause complications such as noduli, fistulation, granuloma, and infection. Some studies postulate that late onset of granulomatous reactions and noduli are more frequent after treatment with permanent filler [6,7]. This study has not been able to confirm the above since we have no information on the total number of treatments and the distribution among the different substances.…”
Section: Discussionmentioning
confidence: 64%
“…However, our study, in line with other studies [2][3][4][5], has shown that dermal filler treatments can have severe side effects and cause complications such as noduli, fistulation, granuloma, and infection. Some studies postulate that late onset of granulomatous reactions and noduli are more frequent after treatment with permanent filler [6,7]. This study has not been able to confirm the above since we have no information on the total number of treatments and the distribution among the different substances.…”
Section: Discussionmentioning
confidence: 64%
“…Although HA fillers are described as nontoxic and nonimmunogenic, some authors have reported hypersensitivity and granulomatous foreign body reactions after the treatment. 3,4,9,11 Adverse reactions to HA fillers may vary and emerge from minor problems related to procedures such as needle marks or pinpoint bleeding, erythema or redness, swelling and edema, pain, tenderness, as well as ecchymosis. 9 These early and immediate adverse reactions are uncommon and occur in only 0.05% to 2% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…7 Delayed reactions occurred in few cases demonstrating hypersensitivity and foreign body reactions, that is, within 6 to 24 months after the injection. 2,4,[9][10][11][12][13][14][15][16][17][18] Authors reported delayed reactions in 0.6% of the cases. 9,19 In this article, we report 2 cases of delayed adverse reactions related to the use of HA filler (Restylane) with oral manifestation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This massive edema was probably initiated by the same pathway as proposed for the inflammatory reaction in case of injection near an old Bio-alcamid injection. The acute inflammatory reaction might be based on a bacterial biofilm or structured colonies of microorganisms encapsulated in an extracellular matrix that surrounds a foreign body and leads to a low-grade chronic infection and injury-mediated reactivation [7]. The hypothesis of role of a biofilm has been suggested, but evidence for the role of a biofilm in late reactions in polyacrylamide is far from settled compared to the evidence for a biofilm in shelled silicone implants.…”
Section: Discussionmentioning
confidence: 99%